2021
DOI: 10.1039/d0nj05548d
|View full text |Cite
|
Sign up to set email alerts
|

Insights into flibanserin oxidative stress degradation pathway: in silicoin vitro toxicity assessment of its degradates

Abstract: Characterization of the degradation products of pharmaceutical drugs is essential to assess their safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Moreover, it has been observed that FLB is quite stable against UV light, acidic and basic environments, and moisture and does not give any degradation products. The results obtained here are similar to the literature, because no degradation product has been found in the stability-indicating studies of FLB until today ( 11 , 21 , 22 ).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Moreover, it has been observed that FLB is quite stable against UV light, acidic and basic environments, and moisture and does not give any degradation products. The results obtained here are similar to the literature, because no degradation product has been found in the stability-indicating studies of FLB until today ( 11 , 21 , 22 ).…”
Section: Resultssupporting
confidence: 91%
“…In the stability-indicating studies on FLB, the forced degradation conditions were carried out in four different ways: 3% H 2 O 2 at 100°C ( 17 ), 3% H 2 O 2 ( 11 ) and 15% H 2 O 2 in a water bath, and 3% H 2 O 2 ( 19 ) and 2.4% H 2 O 2 ( 13 ) at room temperature, previously. The degradation products obtained were broken up of FLB at high temperatures under the forced oxidative conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal care and experimental procedures were approved by the Institutional Research Ethics Committee at the Faculty of Pharmacy Suez Canal University, ethical approval number 201903MA1. The median lethal dose (LD50) of ISO in rats was found to be 600 mg/kg S.C. [84], and the LD50 of FLP in rats is 3.844 g/kg orally, while and maximum tolerated dose of FLP in rats is 0.058 g/kg [85], FLP dose selection was based on previous experiments [86][87][88][89].…”
Section: Experimental Animalsmentioning
confidence: 99%
“…The colorimetric analysis yields a total protein mass estimate that is proportional to the number of cells present. FVP and its breakdown products (FDP 1 and FDP 2) were tested in vitro against NHSF cell lines to determine their potential toxicity and/or safety (Ahmed et al 2020 ; Mohammed F. El-Behairy et al 2021 ). The effect of these chemicals on the viability and proliferation of the NHSF cell line was assessed using the SRB assay, as well as photos taken with an optical microscope to detect any morphological changes on the examined cells.…”
Section: Cytotoxicity Assaymentioning
confidence: 99%